2009
DOI: 10.1183/09031936.00054108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of macrolide therapy on mortality for patients with severe sepsis due to pneumonia

Abstract: Recent studies suggest that macrolides may have beneficial effects for patients at risk for certain infections. The current authors examined the effect of macrolide therapy on 30-and 90-day mortality for patients with severe sepsis caused by pneumonia.A retrospective cohort study was conducted at two tertiary teaching hospitals. Eligible subjects were admitted with a diagnosis of, had chest radiography consistent with, and had a discharge diagnosis of pneumonia and clinical criteria of severe sepsis. Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
2
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(126 citation statements)
references
References 28 publications
(50 reference statements)
2
112
2
9
Order By: Relevance
“…12,14,15 This finding was not supported by the results of the present study, which included only HIV-infected patients.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…12,14,15 This finding was not supported by the results of the present study, which included only HIV-infected patients.…”
Section: Discussioncontrasting
confidence: 56%
“…This study demonstrated a lower 30 and 60-day mortality with the use of macrolides, even among patients who had severe sepsis caused by a microorganism resistant to this antibiotic class (hazard ratio: 0.10; 95% CI: 0.02-0.49; p = 0.005). 15 The immunomodulatory effects of macrolides are yet to be clarified, as there are studies that suggest interference with neutrophil action 16,17 and another study that demonstrates a decrease in pneumolysin production by Streptococcus pneumoniae. 18 A study in particular demonstrates that azithromycin can have a biphasic effect, initially increasing the bactericidal effects of neutrophils and subsequently, when the microorganism has been eliminated, inducing the apoptosis of the latter and interrupting inflammation, leading to a decrease in tissue damage and time of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two large prospective cohort studies showed no difference between these two regimens [66,67]. In a retrospective study in patients with severe sepsis owing to pneumonia caused by any microorganism, macrolide use was associated with decreased mortality, even in patients with macrolideresistant pathogens [68]. In a prospective observational study, Martin-Loeches et al [69] found a lower mortality rate in intubated patients with severe CAP who were treated with combination therapy including macrolides compared with patients treated without macrolide antibiotics.…”
Section: Macrolide Antibioticsmentioning
confidence: 99%